Terpenoids and other secondary metabolites produced by the Eutypella fungi and their bioactivities - Zhou, Yuwei; He, Jingxin; Cui, Hui (Frontiers in Marine Science, 2022)
The fungi Eutypella could metabolize a myriad of natural products with unique structures and diverse bioactivities, which were deemed as key sources for lead compounds in drug discovery. Since the first research on the genus Eutypella in 2009, a myriad of secondary metabolites including terpenoids, alkaloids, and polyketides have been discovered in this genus, and most of them exhibited significant pharmacological activities. However, there are no systematic reviews that reported about the structures and bioactivities of Eutypella up to now. In this review, a total of 153 secondary metabolites and 42 references have been systematically summarized, and we found that the terpenoids (68.09%) and alkaloids (19.15%) were the new main components of this fungi, and the primary antiproliferative activity (64.89%) was mainly derived from the terpenoids and alkaloids. Thus, this review about the chemical diversity and biological activities of the metabolites from the fungus Eutypella provided a new perspective for the development of new drugs for pharmacologists.